2021
DOI: 10.1038/s41598-021-88169-9
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Functional expression of the transient receptor potential ankyrin type 1 channel in pancreatic adenocarcinoma cells

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…From this study, TRPA1 emerged as a tumor-suppressor protein and its activation may be helpful for better therapy. In agreement with these results, TRPA1 decreased cell proliferation and migration in pancreatic adenocarcinoma cells [65]. Opposite results were obtained from breast cancer cells, where inhibition of TRPA1 reduced tumor growth [107].…”
Section: Redox Trp Channels and Inflammationsupporting
confidence: 79%
See 1 more Smart Citation
“…From this study, TRPA1 emerged as a tumor-suppressor protein and its activation may be helpful for better therapy. In agreement with these results, TRPA1 decreased cell proliferation and migration in pancreatic adenocarcinoma cells [65]. Opposite results were obtained from breast cancer cells, where inhibition of TRPA1 reduced tumor growth [107].…”
Section: Redox Trp Channels and Inflammationsupporting
confidence: 79%
“…These results prove that apoptosis induced by TRPA1 is related to Ca 2+ signaling and to channel conducting properties of TRPA1. However, in pancreatic adenocarcinoma cells, the process is different: downregulating TRPA1 with siRNA, decreased cellular viability, and possibly, apoptosis, as revealed by cell cycle analysis [65]. These demonstrated that TRPA1 expression is important in the proliferation and apoptosis of pancreatic ductal adenocarcinoma cells without activation with specific agonists.…”
Section: Apoptosis Induced By Modulation Of the Redox Trp Channelsmentioning
confidence: 98%